Chemistry and Microbiology Qualities of Hard Candy-Green-Sirih Leaves (Piper betle L.) As Cattle Feed Additive - Anika Prastyowati; Lorensia Maria Ekawati Purwijantiningsih; Fransiskus Sinung Pranata (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
Cattle diseases caused by bacterial infection and unqualified feed can decrease production of beef which people consume more in Indonesia. This research objective is to know quality of hard candy as cattle feed additive including chemistry and microbiology characteristics. Research steps consist of material preparation test, making sirih leaf extract, making hard candy, chemistry tests (The levels of water, ashes, reduction sugar, sacarose and atsiri oil, respectively) and microbiology test (Total count test, and yeast and Fungi Test). Theresults showed that hard candy made fulfill SNI (Indonesia National Standar) considered of water level, ashes level, sacarose level, total count, and yeast fungi level. Atsiri oil level before sirih leaves are made into hard candy is 0,405% and it still exists in hard candy with increasing atsiri oil level, 0,1333%.